A Study of the Iron Forging for Sustainable Cultural Tourism Case Study: Ban Had Hien Luang Prabang - BOUNTHIDETH, Thepduangchan; SOMSAMONE, Vilayphone; LOUNBANDITH, Nouphith (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
This research aims to gain the understanding of production of Iron forging handicraft which is local mentality of Hand Hien Village which nearly disappear. These to be information for history educate and appreciable of necessary for conserve, to support the practice in promote planning of extensive cultural travel place in Luang Prabang. The objectives: 1) Study of wrought Iron forging handicraft production 2) Cause factors causing the decrease of the Iron forging career in the community 3) Purpose the promote guidelines and suggestion to conserve for sustainable cultural travel. As qualitative study, apply structural interview and Credibility verify as saturated data together with field work – observation. Descriptive analysis has been applied for description the data from the study. The result of the study show that Iron forging is interweave handicraft between antique and the machine equipment apply human labor; the product are provides for specific consumer and local purchasers; there are several factors that resulted to decrease of Iron forging career as lack of continuation of duration and clear production plan, the entrepreneur changes to do other occupation and new generation not interesting to inherit the career. The guideline and suggestion: include participation to integrate knowledge of Iron forging as activity for education and workshop with tourism. The people should be cultivated promote local mentality inheritance from generation to generation of the awareness of local culture value. Promote the handicraft by media channel with network with relevant organization for cultivated toward economic harmony and local tourism sustainable.